PERCEPTION OF EMPLOYEES TOWARDS UPSKILLING IN IT INDUSTRY WITH REFERENCE TO COIMBATORE CITY - RAJI NP; Dr. N. Rajendran (IJRDO - Journal of Business Management, 2025)
The rapid advancements in the IT industry demand constant upskilling and reskilling of employees to stay competitive. This study explores the perception of employees towards upskilling initiatives within the IT sector, focusing on Coimbatore city. Through surveys and interviews with employees in various IT companies, the research identifies factors influencing their attitudes toward skill enhancement programs, such as career growth, technological changes, and organizational support. The findings highlight the importance of continuous learning, with most employees recognizing its value for professional development and job security. However, challenges like time constraints, lack of awareness, and insufficient training resources were also noted. The study emphasizes the need for effective upskilling strategies, including customized training programs, to align with the rapidly changing demands of the IT industry